A Nationwide Survey of the Severity, Comorbidity, and Mortality of Hospitalized Patients with Asthma in Taiwan - Hui-Ju Hsiao; Li-Chieh Wang; Yao-Hsu Yang; Jyh-Hong Lee; Hsin-Hui Yu; Yu-Tsan Lin; Bor-Luen Chiang (Pediatrics and Neonatology)
To clarify the epidemiology of asthma admission in a nationwide survey, we analyze the characteristics of hospitalized patients in Taiwan. Methods: Data regarding asthma-associated hospitalizations were obtained from the National Health Insurance Research Database of Taiwan from January 2001 to December 2002. Patient characteristics in terms of severity, mortality, and cost were stratified by age, gender, and presence of comorbidities. Results: A total of 59,983 hospitalizations with International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code 493.xx and asthma-related treatment were included in the current analysis. When stratified by age, the number and duration of hospitalizations were distributed in J-shape distribution, with the nadir located in the range of 8–18 years of age. The severity of asthma was found to increase with age (p < 0.001) and was more severe in men compared with women (p < 0.001). The severity of in-hospital patients was significantly greater in subjects with underlying respiratory disease compared to patients with other comorbidities, such as cardiovascular disease and infectious disease. The mortality rates of all hospitalized asthma patients and pediatric hospitalized asthma patients were 0.77% and 0.02%, respectively. The risk factor for mortality of asthma was older age and male gender in multiple regression. Conclusion: The severity of asthma increased after 18 years of age. Increased comorbidities in elderly patients might contribute to asthma severity. The mortality rate was low in pediatric patients and significantly increased in males and the elderly. The above findings suggest that additional effort is required in the treatment of elderly and male asthmatic patients.